2017
DOI: 10.1242/dev.146761
|View full text |Cite
|
Sign up to set email alerts
|

Actomyosin-based tissue folding requires a multicellular myosin gradient

Abstract: Tissue folding promotes three-dimensional (3D) form during development. In many cases, folding is associated with myosin accumulation at the apical surface of epithelial cells, as seen in the vertebrate neural tube and the Drosophila ventral furrow. This type of folding is characterized by constriction of apical cell surfaces, and the resulting cell shape change is thought to cause tissue folding. Here, we use quantitative microscopy to measure the pattern of transcription, signaling, myosin activation and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
131
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(143 citation statements)
references
References 52 publications
12
131
0
Order By: Relevance
“…A requirement for cell ratcheting to maintain uniform furrow behaviors Previous work has demonstrated that a gradient of forces is present across the incipient furrow during mesoderm invagination in Drosophila (Heer et al, 2017). As cells will experience different pulling forces across this gradient, we questioned whether a requirement for cell ratcheting would be equally present in apically constricting cells.…”
Section: Sbf Directly Associates With Rab35 and Increases Gtp Exchangmentioning
confidence: 95%
“…A requirement for cell ratcheting to maintain uniform furrow behaviors Previous work has demonstrated that a gradient of forces is present across the incipient furrow during mesoderm invagination in Drosophila (Heer et al, 2017). As cells will experience different pulling forces across this gradient, we questioned whether a requirement for cell ratcheting would be equally present in apically constricting cells.…”
Section: Sbf Directly Associates With Rab35 and Increases Gtp Exchangmentioning
confidence: 95%
“…30 Equations of motion are obtained variationally from energy functionals based on the standard Koiter shell model. [31][32][33] Elastic dynamics are overdamped, consistent with growth processes in both living and engineered systems. 28 As a consequence, it is assumed at any time t that the system is in its minimal energy configuration.…”
Section: Modelmentioning
confidence: 74%
“…28 As a consequence, it is assumed at any time t that the system is in its minimal energy configuration. For our system, these energy functionals are given in terms of the difference between the instantaneous metric a and curvature b tensors of the surface, and prescribed reference tensors % a and % b which define the local equilibrium behavior: 32,34…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Contraction of the actomyosin cytoskeleton drives cell and tissue movements during morphogenesis (Siedlik and Nelson, 2015;Heer et al, 2017) and wound closure (Russo et al, 2005), and allows cells to perceive and respond to mechanical stress (Clark et al, 2007). In non-muscle cells, cell contraction is driven by the interaction of the motor protein, non-muscle myosin II (NMII), with filamentous actin.…”
Section: Introductionmentioning
confidence: 99%